Patent Foramen Ovale With Atrial Septal Aneurysm Is Strongly Associated With Migraine With Aura: A Large Observational Study - Roel J. R. Snijder; Justin G. L. M. Luermans; Albert H. de Heij; Vincent Thijs; Wouter J. Schonewille; Alexander Van De Bruaene; Martin J. Swaans; Werner I. H. L. Budts; Martijn C. Post (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background A patent foramen ovale (PFO) with atrial septal aneurysm (ASA) has been identified as a risk factor for cryptogenic stroke. Patients with migraine with aura (MA) appear to be at risk for silent brain infarction, which might be related to the presence of a PFO. However, the association between MA and PFO with ASA has never been reported. We examined this association in a large observational study. Methods and Results Patients (>18 years) who underwent an agitated saline transesophageal echocardiography (cTEE) at our outpatient clinics within a timeframe of 4 years were eligible to be included. Before cTEE they received a validated headache questionnaire. Two neurologists diagnosed migraine with or without aura according to the International Headache Criteria. A total of 889 patients (mean age 56.4±14.3 years, 41.7% women) were included. A PFO was present in 23.2%, an isolated ASA in 2.7%, and a PFO with ASA in 6.9%. The occurrence of migraine was 18.9%; the occurrence of MA was 8.1%. The prevalence of PFO with ASA was significantly higher in patients with MA compared to patients without migraine (18.1% vs 6.1%; OR 3.72, 95% CI 1.86‐7.44, P<0.001). However, a PFO without ASA was not significantly associated with MA (OR 1.50, 95% CI 0.79‐2.82, P=0.21). Interestingly, a PFO with ASA was strongly associated with MA (OR 2.71, 95% CI 1.23‐5.95, P=0.01). Conclusion In this large observational study, PFO with ASA was significantly associated with MA only. PFO closure studies should focus on this specific intra‐atrial anomaly.